The Emergence of The Pancasila Student Profil Through The RADEC Learning Model Using E-learning on Soil Materials at Muhammadiyah 6 Palembang Elementary School - Rifatul Mahmudah; Atep Sujana; Babang Robandi; Wahyu Sopandi (International Conference on Elementary Education, 2023)
The emergence of the Pancasila Student Profil through the Radec Learning Model Using E-Learning on Soil Materials at Muhammadiyah 6 Palembang Elementary School. The purpose of this study was to see the emergence of the Pancasila Student Profil at each stage of the RADEC learning model at SD Muh 6 Palembang. This type of qualitative research is descriptive using a purposeful sampling technique. From this study, the results obtained: The dimensions that arise when students follow the stages of reading learning are faith, fear of God Almighty, and noble character, independent, mutual cooperation, global sustainability, critical reasoning, and creative. The dimension that arises when students follow the answer learning stages is faithful, devoted to God Almighty, and has noble character, is independent, mutual cooperation, is globally sustainable, has critical reasoning, and creative. The dimensions that arise when students take part in the discuss and explain learning stages are faith, fear of God Almighty, and noble character, independent, mutual cooperation, global sustainability, critical reasoning, and creativity. The dimensions that arise when students follow the create learning stage are faith, fear of God Almighty, and noble character, independent, mutual cooperation, global sustainability, critical reasoning, and creative.